Migration characteristics of oil pollutants into soil pores influenced by surface wettability. Issue 1 (31st December 2022) - Lin, Lin; Pu, Yu; Wang, Di; Guo, Xi; Wang, Peng; Lu, Zhong
ABSTRACT: Pore-scale modeling plays an indispensable role in unveiling the migration mechanism of oil pollutants into the water-saturated soil. Navier Stokes equations and conservation of mass, coupled with the phase field method, are employed to investigate the effect of soil wettability on oil pollutants migration into the soil porous media. The results show that the oil-water interface in the migration process does not advance evenly in three wetting states. When the model system is in oil-wetting state, oil pollutants obviously migrate at a higher speed. Through monitoring the evolution of oil front location and analyzing the velocity distribution vertical to the flow direction at the central axis of the model, the channel corresponding to the peak velocity is the dominant flow channel for the oil pollutants. This study will have the potential ability in obtaining the pore-scale migration regulation of oil pollutions as well as more accurately predicting the pollution range.